Purification of raw palygorskite: a comparative study involving different processes and dispersing agents - G. P. M. de Souza; T. F. da Silva; A. P. F. Albers; E. Quinteiro; F. R. Passador (Cerâmica, 2021)
Abstract Palygorskite (Pal) is a natural clay mineral with fibrous morphology and high surface area. Depending on the geological origin, it presents impurities, such as quartz and carbonates, which can harm some of its properties. Therefore, this work seeks to define a viable methodology for the purification of a Brazilian Pal. Two types of mixing processes (sonication and milling) and two types of dispersing agents (sodium silicate and sodium polyacrylate) were investigated. In addition, a subsequent acid activation with hydrogen peroxide and sulfuric acid was performed for complete purification. The viability of the purification of Pal was confirmed by X-ray diffraction, X-ray fluorescence, and thermogravimetric analyses. The sonication mixture process and the use of sodium polyacrylate as a dispersing agent were more effective. In addition, BET analysis showed an increase in the surface area of Pal, and scanning electron microscopy confirmed the permanence of its fibrous morphology after the purification steps.